Influence of skin cold sensation threshold in the occurrence of dental sensitivity during dental bleaching: a placebo controlled clinical trial - Rahal, Vanessa [UNESP]; Gallinari, Marjorie de Oliveira [UNESP]; Barbosa, Juliana Stuginski; Martins-Junior, Reynaldo Leite; Santos, Paulo Henrique dos [UNESP]; Angelo Cintra, Luciano Tavares [UNESP]; Fraga Briso, Andre Luiz [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2018)
Objective: This study verified the occurrence of dental sensitivity in patients submitted to a 35% hydrogen peroxide based product (Whiteness HP Maxx 35% - FGM), skin cold sensation threshold (SCST) and its influence on dental sensitivity. Material and Methods: Sixty volunteers were divided into 4 groups (n=15), according to SCST (low: GI and GIII, and high: GII and IV) and bleaching treatment (hydrogen peroxide: GI and GII, and placebo: GIII and GIV). SCST was determined in the inner forearm for 6 different times using a neurosensory analyzer, the TSA II (Medoc Advanced Medical Systems, Ramat Yishai, Northern District, Israel). Dental sensitivity measurements were performed 10 different times using a thermal stimulus and an intraoral device attached to TSA II, positioned in the buccal surface of the upper right central incisor. Spontaneous dental sensitivity was also determined using the Visual Analogue Scale (VAS). Data were submitted to Student's t-test and Pearson's Correlation Test (a=0.05). SCST remained the same during bleaching treatment. Results: Distinct responses of dental sensitivity were found in patients with low and high SCST during the first and third bleaching session (p=0.05). The teeth submitted to the bleaching treatment became more sensitive to cold than those treated with placebo. Moreover, data obtained with TSA and VAS presented moderate correlation. Conclusions: Bleaching treatment increased dental sensitivity and skin cold sensation threshold might represent a determining factor in this occurrence, since low and high SCST patients had different responses to the thermal stimulus in the teeth.
Keywords: Clinical trial; Dental bleaching; Sensation; Quantitative analysis